Influence of Cu Content on the Microstructure and Mechanical Properties of Cr-Cu-N Coatings. (14th January 2018) - Ding, Ji Cheng; Zhang, Teng Fei; Wan, Zhi Xin; Mei, Hai Juan; Kang, Myung Chang; Wang, Qi Min; Kim, Kwang Ho
Abstract : The Cr-Cu-N coatings with various Cu contents (0–25.18 (±0.17) at.%) were deposited on Si wafer and stainless steel (SUS 304) substrates in reactive Ar+N2 gas mixture by a hybrid coating system combining pulsed DC and RF magnetron sputtering techniques. The influence of Cu content on the coating composition, microstructure, and mechanical properties was investigated. The microstructure of the coatings was significantly altered by the introduction of Cu. The deposited coatings exhibit solid solution structure with different compositions in all of the samples. Addition of Cu is intensively favored for preferred orientation growth along (200) direction by restricting in (111) direction. With increasing Cu content, the surface and cross-sectional morphology of coatings were changed from triangle cone-shaped, columnar feature to broccoli-like and compact glassy microstructure, respectively. The mechanical properties including the residual stress, nanohardness, and toughness of the coatings were explored on the basis of Cu content. The highest hardness was obtained at the Cu content of 1.49 (±0.10) at.%.